Characterizing Chinese undergraduate students’ empathizing-systemizing profiles: a person-centered approach - Qin, Yishu; Zhang, Da-Wei (Frontiers in Psychology, 2024)
While the empathising-systemising (E-S) theory provides a valuable framework for explaining gender differences in STEM majors, previous studies suffer from methodological issues (i.e., the arbitrary cut-off criteria and WEIRD sampling) as well as discrepancies in the behavioural correlates of E-S types. To address the gaps, this study utilised a 3-step latent profile analysis to identify naturally occurring E-S profiles in a Chinese sample and explored the predictors and distal outcomes of the identified profiles. The study recruited 785 (aged 18-25 years, 60% female) Chinese undergraduates. Results revealed five E-S profiles: Disengaged, Empathisers, Navigating systemisers, Technological systemisers, and Self-declared allrounders. Controlling for socioeconomic status, being male predicted a higher likelihood of membership into the Technological systemisers. Besides, membership to the Navigating systemisers and Technological systemisers was associated with better intuitive physics performance. However, no significant variation was observed for social sensitivity performance across E-S profiles. Overall, our results partially conformed to previous findings, highlighting the importance of cultural adaptation and methodological considerations when classifying students' cognitive types.